2006
DOI: 10.1002/ange.200602847
|View full text |Cite
|
Sign up to set email alerts
|

Controllable [2+2] Cycloadditions of 1,5‐Bisallenyl‐Substituted Compounds

Abstract: Auf geht's, Allene: Durch gezielte Kopf‐Kopf‐ oder Schwanz‐Schwanz‐[2+2]‐Cycloaddition wurden 1,5‐Bisallenylverbindungen in [3.2.0]‐ bzw. [5.2.0]bicyclische Verbindungen überführt (siehe Schema). Die bicyclischen Produkte enthalten Doppelbindungen, die sich für weitere Umsetzungen eignen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…One of the most interesting advances in the field of cycloaddition reactions is the involvement of [2 + 2] cycloaddition reactions to the generation of different types of functionalized molecules containing heterocyclic or isocyclic rings, which prove to be the most frequently used strategic tools to access four‐membered cyclic compounds in recent years. [ 51 ] In particular, intramolecular [2 + 2] cycloaddition between an allene unit and an alkene or an alkyne moiety represents a powerful and highly atom‐economic approach to furnish cyclobutanes and cyclobutenes under thermal, [ 52‐54 ] photochemical [ 55‐58 ] and transition metal catalyzed [ 59‐62 ] conditions. In 2016, Shi and co‐workers reported an elegant and highly regioselective [2 + 2] cycloaddition of yne‐allenes 33 for the synthesis of spirosubstituted cyclobutenes 34 in good to excellent yields (Scheme 10).…”
Section: Synthesis Of Carbocyclesmentioning
confidence: 99%
“…One of the most interesting advances in the field of cycloaddition reactions is the involvement of [2 + 2] cycloaddition reactions to the generation of different types of functionalized molecules containing heterocyclic or isocyclic rings, which prove to be the most frequently used strategic tools to access four‐membered cyclic compounds in recent years. [ 51 ] In particular, intramolecular [2 + 2] cycloaddition between an allene unit and an alkene or an alkyne moiety represents a powerful and highly atom‐economic approach to furnish cyclobutanes and cyclobutenes under thermal, [ 52‐54 ] photochemical [ 55‐58 ] and transition metal catalyzed [ 59‐62 ] conditions. In 2016, Shi and co‐workers reported an elegant and highly regioselective [2 + 2] cycloaddition of yne‐allenes 33 for the synthesis of spirosubstituted cyclobutenes 34 in good to excellent yields (Scheme 10).…”
Section: Synthesis Of Carbocyclesmentioning
confidence: 99%
“…The results in Table 1 imply that the introduction of two phenylsulfonyl groups on both allenyl functionalities makes the intramolecular carbonylative [2+2+1] cycloaddition between the terminal double bonds of the two allenyl groups extremely smooth. The bulky phenylsulfonyl groups might not only suppress the cyclometalation between the two internal double bonds11d or between a terminal and a internal double bond of two allenyl groups,11c,f,g but might also orient the two terminal double bonds of the allenyl moieties such that they can react. An unexpectedly easy formation of the bicyclo[5.3.0]decadienone framework from bis(allene)s, particularly from bis(phenylsulfonylallene) derivatives, under mild reaction conditions (5 mol % of [{RhCl(CO)dppp} 2 ], 1 atm CO, toluene 80 °C, 1 h) encouraged us to apply this new method to the construction of the bicyclo[6.3.0] skeleton.…”
Section: Rhodium(i)‐catalyzed Synthesis Of Bicyclo[530] Compounds Bmentioning
confidence: 99%
“…The Co 2 (CO) 8 -mediated [2+2+1] cycloaddition of three components-an alkyne p-bond, an alkene p-bond, and carbon monoxide (CO)-is known as the Pauson-Khand reaction, [1] and its intramolecular version provides both the most straightforward and the most powerful methodology for the construction of cyclopentenone-fused bicyclic frameworks (Scheme 1, conversion of 1 into 2). Several transition metals, such as Rh, Ir, Mo, Zr, Ti, and so on, have now been found to be useful catalysts for carbonylative [2+2+1] cycloadditions of this type.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the synthetic versatility of bisA C H T U N G T R E N N U N G (allene)s has recently been demonstrated by the Ma group, [8][9][10][11] who have found that the thermal and Pd-catalyzed [2+2] cycloadditions of 1,5-bisA C H T U N G T R E N N U N G (allene) compounds give rise to the formation of bicycloA C H T U N G T R E N N U N G [5.2.0] and bicycloA C H T U N G T R E N N U N G [3.2.0] frameworks, respectively. [8] Interestingly, they also disclosed that 1,5-bis-A C H T U N G T R E N N U N G (allene)s underwent bimolecular cyclization to afford steroid-like skeletons with the aid of trans-[RhCl(CO)- [9] whereas 1,5-bisA C H T U N G T R E N N U N G (allene) derivatives with substituents at the allenic terminus gave seven-membered cross-conjugated trienes through cycloisomerization when treated with [{RhCl(CO) 2 } 2 ]. [10] Chung and Kang also reported intriguing cycloisomerizations and carbonylative [2+2+1] cycloadditions of 1,5-bisA C H T U N G T R E N N U N G (allene)s. [12] Our contiguous interest in the fields of [{RhCl(CO) 2 } 2 ]-or [{RhCl(CO)dppp} 2 ]-catalyzed allenic cycloadditions [7,13] prompted us to investigate carbonylative [2+2+1] cycloadditions between two allenic p-bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation